Authigenic clay minerals and calcite dissolution influence reservoir quality in tight sandstones: Insights from the central Junggar Basin, NW China - Hong, Dongdong; Cao, Jian; Wu, Tao; Dang, Sisi; Hu, Wenxuan; Yao, Suping (Energy Geoscience, 2020)
Authigenic clays and calcite cements are important in the development of reservoir tightness and the formation of hydrocarbon sweet spots. We investigated Jurassic low-permeability sandstone reservoirs in the central Junggar Basin, NW China, using petrography, mineralogy, porosity, and permeability assessment, and stable C and O isotope analysis to ascertain the influence of authigenic clays and calcites on reservoir quality. Here, we establish the properties and diagenetic processes of the reservoir sandstones, and construct a generalizable model of reservoir quality. The results show that the sandstones are mainly litharenite and feldspathic litharenite and can be classified into ductile-lithic-rich sandstones and ductile-lithic-poor sandstones according to rock composition. The ductile-lithic-rich sandstones are tight (mean porosity = 7.31%; mean permeability = 0.08 mD) as a result of intense compaction. In contrast, the ductile-lithic-poor sandstones can be classified into five types according to diagenetic process. The formation of favorable hydrocarbon reservoir properties is closely related to the presence of authigenic clays and dissolution of calcite. In particular, kaolinite fills intergranular pores, thereby blocking pore space and reducing reservoir quality. Chlorite coating resists compaction and limits the formation of quartz overgrowths, thereby preserving pore space and enhancing reservoir quality. Calcite controls reservoir quality through both precipitation and dissolution. Calcite precipitation results in reduced reservoir quality, whereby early calcites that were precipitated in formation water resist compaction and provide the basis for subsequent dissolution and late precipitation, whereas dissolution of calcite in mesodiagenesis improves reservoir quality. A generalized model is formulated by relating diagenetic facies types to depth and porosity, providing a reference for other similar reservoirs. Our data suggest that deeply buried tight sandstones can be exploration prospects under favorable conditions involving the presence of authigenic clays and dissolution of calcite, as in the central Junggar Basin of this study. [Display omitted] •Authigenic clays and calcite dissolution influence reservoir quality in tight sandstones.•A case study was performed in the central Junggar Basin, China.•Kaolinite fills intergranular pores and reduces reservoir quality.•Chlorite coating resists compaction and limits the formation of quartz overgrowths.•Calcite controls reservoir quality through both precipitation and dissolution.